Diversity of Linum genetic resources in global genebanks: from agro-morphological characterisation to novel genomic technologies – a review - Kaur, Vikender; Singh, Mamta; Wankhede, Dhammaprakash Pandhari; Gupta, Kavita; Langyan, Sapna; Aravind, Jayaraman; Thangavel, Boopathi; Yadav, Shashank Kumar; Kalia, Sanjay; Singh, Kuldeep; Kumar, Ashok (Frontiers in Nutrition, 2023)
Linseed or flaxseed is a well-recognized nutritional food with nutraceutical properties owing to high omega-3 fatty acid (α-Linolenic acid), dietary fiber, quality protein, and lignan content. Currently, linseed enjoys the status of a ‘superfood’ and its integration in the food chain as a functional food is evolving continuously as seed constituents are associated with lowering the risk of chronic ailments, such as heart diseases, cancer, diabetes, and rheumatoid arthritis. This crop also receives much attention in the handloom and textile sectors as the world’s coolest fabric linen is made up of its stem fibers which are endowed with unique qualities such as luster, tensile strength, density, bio-degradability, and non-hazardous nature. Worldwide, major linseed growing areas are facing erratic rainfall and temperature patterns affecting flax yield, quality, and response to biotic stresses. Amid such changing climatic regimes and associated future threats, diverse linseed genetic resources would be crucial for developing cultivars with a broad genetic base for sustainable production. Furthermore, linseed is grown across the world in varied agro-climatic conditions; therefore it is vital to develop niche-specific cultivars to cater to diverse needs and keep pace with rising demands globally. Linseed genetic diversity conserved in global genebanks in the form of germplasm collection from natural diversity rich areas is expected to harbor genetic variants and thus form crucial resources for breeding tailored crops to specific culinary and industrial uses. Global genebank collections thus potentially play an important role in supporting sustainable agriculture and food security. Currently, approximately 61,000 germplasm accessions of linseed including 1,127 wild accessions are conserved in genebanks/institutes worldwide. This review analyzes the current status of Linum genetic resources in global genebanks, evaluation for agro-morphological traits, stress tolerance, and nutritional profiling to promote their effective use for sustainable production and nutrition enhancement in our modern diets.